Application of PCR-Based Techniques for the Identification of Genetic Fingerprint Diversity of Dominant Bacteria in Fecal Samples of Children with Diarrhea in Vietnam - Thi Quy Nguyen; Trong Khoa Dao; Hong Duong Nguyen; Thi Bich Thuy Phung; Thi Thanh Nga Pham; Thi Viet Ha Nguyen; Thi Huong Trinh; Huu Cuong Le; Thi Thu Hong Le; Thi Huyen Do (Infectious Disease Reports, 2024)
In Vietnam, diarrhea, especially persistent diarrhea, is one of the most common diseases in children, while a significant proportion of cases are negative with pathogens; thus, there is an urgent need to understand gut bacterial dysbiosis. In this study, bacteria in the fecal samples of five healthy and ten diarrheal children were separated from other residues, then adopted to extract their metagenomic DNA for evaluating their diversity based on V3 and V6–V8 regions and the 16S rRNA gene by PCR-RFLP and PCR-DGGE. As a result, bacterial metagenomic DNAs with high quality, quantity and diversity were successfully extracted using a GeneJET kit and a chemical protocol. A sequence analysis of 73 representative DNA fragments from gels indicated a remarkable bacterial dysbiosis in all groups of diarrhea. Viral diarrhea was characterized by extremely reduced bacterial diversity with the blossom of Bifidobacterium and Streptococcus. Streptococcus was also the most abundant in persistent diarrhea. Beneficial bacteria that may play a role in the self- rebalance in intestinal bacterial communities, such as Bifidobacterium, Lactobacillus, and Enterococcus, were seen in all diarrheal groups, while Bacteroides and Akkermansia muciniphila were seen in the healthy group but absent in the diarrheal groups. This study provides additional evidence for a relationship between intestinal bacterial dysbiosis and diarrhea in children, emphasizing an increase in Streptococcus.